Eating perception and psychiatric morbidity in secondary school and medical students in Kelantan - Naing, Khin Ohnmar@Noor Jan; Md. Zain, Azhar; Naing, Nyi Nyi; Kumaraswamy, Narasappa; Jamil@Osman, Zubaidah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2008)
Introduction: A significant concern about body weight and shape is the pathognomonic feature of eating disorders. According to the cognitive view, ideation and belief component is the primary cause for the development and maintenance of eating disorders. Higher psychiatric morbidity and psychological stress increases the development of eating disorders. Objective: This study was conducted to examine whether there is a relationship between psychological stress and cognitive aspect of eating, and between secondary and tertiary students. Methods: A cross-sectional study was carried out to determine beliefs about weight and shape concerns among secondary and tertiary level students. A total of 1253 students consisting of 13-18 years old secondary school students and 19-24 years old medical students were involved in this study. The students completed a questionnaire assessing psychopathology on beliefs and attitudes towards weight and shape and General Health Questionnaire (GHQ-30). Results: The results indicate a high prevalence of psychiatric morbidity among university students compared to secondary students. Year 1 medical students appear to have a higher frequency of psychiatric morbidity (53.9%) than year 4 medical students (28.4%). Eating beliefs relating to weight and shape were significantly higher in secondary school students than medical students. The results of multiple linear regression on the eating belief questionnaire were a significant predictor of psychiatric morbidity. Higher GHQ scores were negatively related to eating belief question 28 of bulimic component. Conclusion: It would be useful to conduct future studies to explore the possible causal factors for weight and shape concerns among secondary school students and higher psychiatric morbidity among medical students in Kelantan.